Pengaruh penggunaan AD-Pharm Hypertension Mobile Health Application terhadap tingkat kepatuhan minum obat pasien hipertensi di Puskesmas Kota Yogyakarta - Wigka Pawestri, Novianti; Zukhruf Saputri, Ginanjar; Hidayati, Ana; Muhammad Irham, Lalu; Hanisari, Putri; S, Yuni; Galuh, Tiwi; Sany (Pharmasipha : Pharmaceutical Journal of Islamic Pharmacy, 2025)
The prevalence of hypertension in Indonesia is still quite high. One of the causes of the high incidence of hypertension is patient’s nonadherence in their treatment, such as forgetting to take medication. The patient's medication adherence determines the success of hypertension therapy. AD-Pharm Hypertension Mobile Health Application contains several features, one of which is a reminder to remind patients to take medication. The purpose of this study was to determine the effect of the AD-Pharm Hypertension Mobile Health Application on the level of medication adherence of hypertension patients in 4 public health centers in Yogyakarta.  This research method is a quasi-experimental pre-post design with a control group. The sampling technique was consecutive sampling involving 100 respondents, of which 50 respondents were the control group and 50 were the intervention group. The intervention that is given is AD-Pharm hypertension mobile health application. Data were collected using the MARS-5 questionnaire which were analyzed using Mann Whitney test and the Wilcoxon test. The results of the analysis showed that there was a significant difference (p=0.001) of medication adherence between the pre and post-test of the intervention group from 23.96±1.525 to 24.46±1. While in the control group there was no significant difference (p=0.059), from 24.04±1.142 (pre-test) to 24.16±0.976 (post-test). Based on the results of this study, it can be concluded that there is a significant effect on the use of AD-Pharm Hypertension Mobile Health Application on the level of medication adherence of hypertension patients.